2013
DOI: 10.1002/dmrr.2395
|View full text |Cite
|
Sign up to set email alerts
|

Common mechanisms of dysfunctional adipose tissue and obesity‐related cancers

Abstract: The relation between cancer and metabolic disorders was recognized several decades ago, but the underlying mechanisms involved in cancer development and progression remain obscure. In the last years, many groups have been studying systemic adipose tissue markers in cancer patients. However, few consistent results were obtained. On the other hand, several studies revealed many aspects of adipose tissue physiology in obesity. Nowadays, it is recognized that excessive lipid uptake in adipocytes leads to hypertrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 118 publications
(337 reference statements)
0
39
0
Order By: Relevance
“…It was observed that in BC patients, visceral fat rating was associated with some BC characteristics, including hormone receptor status and tumor stage at diagnosis. The increase of visceral adipose tissue has been associated with hyperinsulinemia and insulin resistance, factors associated with an increase in BC risk [8]. Insulin exerts a direct mitogenic effect on BC cells, has a synergistic activity with estrogens, and can indi- rectly affect tumorigenesis by contributing to the synthesis and activity of IGFs I and II.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that in BC patients, visceral fat rating was associated with some BC characteristics, including hormone receptor status and tumor stage at diagnosis. The increase of visceral adipose tissue has been associated with hyperinsulinemia and insulin resistance, factors associated with an increase in BC risk [8]. Insulin exerts a direct mitogenic effect on BC cells, has a synergistic activity with estrogens, and can indi- rectly affect tumorigenesis by contributing to the synthesis and activity of IGFs I and II.…”
Section: Discussionmentioning
confidence: 99%
“…A number of hypotheses have been proposed to explain this link 2, 3 , including the high production of several factors, such as adipokines and inflammatory cytokines, by excess adipose tissue in the obese individuals 3,10,11 . In obesity, adipose tissue becomes dysfunctional, which results in metabolic and inflammatory changes that increase oxidative stress and the production of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, HIF-1a was associated with an increase occurrence of metastases. Furthermore HIF-1a inhibition might improve sensitivity of tumors to radiation 37,41.…”
Section: Introductionmentioning
confidence: 99%
“…There is an axis between white hypertrophic adipocytes secreting inflammatory proteins and functional status of the endothelium of the capillaries and systemic fat 125. The inflammatory proteins secreted by hypertrophic and hypoxic white adipocytes are the primary cause of atherosclerosis, state of insulin resistance, high blood pressure, type 2 diabetes mellitus, metabolic syndrome, bone joint and muscle tendon degeneration 126-128. Furthermore links between obesity and inflammation and between chronic inflammation and cancer may suggest that inflammation may be important in linking obesity to cancer 129-132.…”
Section: Introductionmentioning
confidence: 99%